Use of Interrogative Sentences in Mass Media Texts - Bitinienė, Audronė (Kalbotyra, 2004)
The article presents an analysis of a possible way of prosaic dialogisation in mass media texts by the employment of question-answer fragments in monologue. It also discusses the structure of such fragments and their partial functions in text organisation.